Cabinet Formation in Indonesia's Presidential System: A Comparative Study of the 1945 Constitution Before and After Constitutional Amendments: Pembentukan Kabinet dalam Sistem Pemerintahan Presidensil di Indonesia: Studi Komparasi UUD 1945 Sebelum Dan Setelah Perubahan - Firdaus Arifin (Lex Renaissance, 2024)
The amendment to the 1945 Constitution brought significant changes to the cabinet formation mechanism in Indonesia, especially related to the checks and balances between the executive and legislative power. Before the amendment, the president had a broad authority in forming a cabinet without parliamentary oversight, which often led to centralization of power and low accountability. This study aims to analyze the impact of the amendment to the 1945 Constitution on the President's authority in forming a cabinet and how these changes affect the stability and effectiveness of government. Using a normative legal research approach with a comparative method, this study compares the periods before and after the amendment to explore the role of the legislature in the cabinet formation process. The results show that although the amendment strengthened the principle of democracy by increasing the House of Representatives' oversight, it also caused political fragmentation that hampered the process of political negotiation and government effectiveness. The implications of this study indicate the need for further reform in governance to ensure cabinet stability and improve government efficiency without compromising democratic principles.Keywords: Government System, Presidential, Parliamentary, Constitution Abstrak. Amandemen UUD 1945 membawa perubahan signifikan dalam proses pembentukan kabinet di Indonesia, terutama terkait dengan mekanisme checks and balances antara eksekutif dan legislatif. Sebelum amandemen, presiden memiliki kewenangan yang sangat luas dalam pembentukan kabinet tanpa pengawasan parlemen, yang sering menimbulkan sentralisasi kekuasaan dan rendahnya akuntabilitas. Penelitian ini bertujuan untuk menganalisis dampak amandemen UUD 1945 terhadap kewenangan presiden dalam pembentukan kabinet dan bagaimana perubahan ini memengaruhi stabilitas serta efektivitas pemerintahan. Menggunakan pendekatan penelitian hukum normatif dengan metode komparatif, penelitian ini membandingkan periode sebelum dan sesudah amandemen untuk mengeksplorasi peran legislatif dalam proses pembentukan kabinet. Hasil penelitian menunjukkan bahwa meskipun amandemen memperkuat prinsip demokrasi dengan meningkatkan pengawasan DPR, hal ini juga menyebabkan fragmentasi politik yang menghambat proses negosiasi politik dan efektivitas pemerintahan. Implikasi dari penelitian ini menunjukkan perlunya reformasi lebih lanjut dalam tata kelola pemerintahan untuk memastikan stabilitas kabinet dan meningkatkan efisiensi pemerintahan tanpa mengurangi prinsip-prinsip demokrasi.Kata Kunci: Sistem Pemerintahan, Presidensial, Parlementer, Konstitusi